Bovine immunisation with a recombinant peptide derived from synthetic SBm7462® (Bm86 epitope construct) immunogen for Rhipicephalus microplus control (2020)
Rhipicephalus microplus: is the most important ectoparasite of livestock in tropical and subtropical areas around the world. Research focused on developing an efficient vaccine for cattle tick control is a high priority. The aim of this study was to evaluate the rSBm7462® peptide (Bm86-B and T cell epitopes) regarding its properties of immunogenicity, protective effect in cattle and efficacy against R. microplus. This peptide was produced by a fermentative process in the yeast culture system of Komagataella (Pichia) pastoris strain Km 71. The vaccination assay was conducted in a tick-free area using non-splenectomised Holstein Friesian calves, separated into immunisation and control groups. These animals individually received the recombinant peptide and the inoculum without peptide using saponin as an adjuvant at three time points. The calves were challenged 21 days after the last immunisation using 4500 larvae per animal. An indirect ELISA was used to identify the IgG kinetics of serum samples from the calves studied. The qPCR was performed to determine the cytokine gene expression from the total RNA of the cultured PBMCs. Histomorphometry of the germinal centres (GCs) was performed measuring slides with haematoxylin-eosin staining of surgically removed lymph nodes from immunised calves. The antibody response showed a significant induction of high-affinity IgGs in calves immunised with the recombinant peptide in comparison to the controls. The kinetics of antibodies in immunised calves showed a significant increase during the experiment. This increase in high-affinity IgGs correlated with a gradual increase of the GC diameter following each peptide vaccination. Cytokine expression profiles demonstrating an adaptive immune response in calves immunised with rSBm7462® confirmed the T-dependent response. Vaccine efficacy was calculated at 72.4 % following the analysis and fecundity of collected adult female ticks, compared between control and vaccinated groups. These findings demonstrate that this new recombinant peptide is an option for control of R. microplus infestations.